The Slave Metaphor and Gendered Enslavement in Early Christian Discourse - Bjelland Kartzow, Marianne, author.
1 online resource
Keywords: "The Slave Metaphor and Gendered Enslavement in Early Christian Discourse adds new knowledge to the ongoing discussion of slavery in early Christian discourse. Bjelland Kartzow argues that the complex tension between metaphor and social reality in early Christian discourse is undertheorized. A metaphor can be so much more than an innocent thought figure, since it involves bodies, relationships, life stories, and memory in complex ways. This study rethinks the potential meaning of the slavery metaphor in early Christian texts, by use of a variety of texts, read with a whole set of theoretical tools, taken from metaphor theory and intersectional gender studies, in particular. It also takes seriously the contemporary context of Modern Slavery, where slavery has re-appeared as a term to name trafficking, gendered violence, and inhuman power systems."--Provided by publisher.